Strategi Pembelajaran Daring Anak Usia Dini pada Masa Pandemi Covid-19 - Safriyani, Rizka; Wakhidah, Elfa Wahyu; Supriyanto, Catur (Musamus Journal of Primary Education, 2021)
In the pandemic era, schools are implementing online learning strategies including at the Early Childhood Education level. Online learning for children of course presents its own challenges for the teaching teachers. This study aims to investigate online learning strategies at the play group level. The method in this research uses qualitative research that describes what strategies are used in online learning and its application in the NU 104 Al-Firdaus Muslimat Playgroup. Data collection techniques used in this study were observation, interviews, and documentation. The results of this study indicate that the Muslimat NU 104 Al-Firdaus Play Group uses video or photo media and the results of children's activities are sent by parents to the teacher via video or photos via the Whatsapp application. The activities carried out included singing, telling stories with parents, working on worksheets, and experimenting with making hand sanitizers. For parents who do not have a mobile device, home visits are carried out by the teacher with the same activities, namely singing, telling stories with parents, working on worksheets, and experimenting with making hand sanitizers.